UPAYA MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA DINI MELALUI PERMAINAN LABIRIN - Husnul Hafidhoh; Suyadi (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to determine the role of labyrinth games in improving cognitive abilities of early childhood on the subject of recognizing geometric shapes, numbers 1-10 and various animals at RA Imama Mijen Semarang. To obtain data in this study using the method of classroom action research (CAR) from data through observation and interviews. This research was conducted in group B RA IMAMA Mijen Semarang with a total of 15 people. The results showed that children's cognitive development increased after the action through the maze game. At the time of pre-action observation the percentage of cognitive development was 35.40%. then it experienced an increase in cycle 1 of 50.16%, and in the implementation of cycle II it experienced a very good increase of 81.34%. steps taken so that children's cognitive development increases: pre-development activities, development activities, and closing activities. Active briefing is carried out during development activities and during closing activities.